Relationship Between Vitamin D Status and Vitamin D Receptor Gene Polymorphisms With Markers of Metabolic Syndrome Among Adults - Karonova, Tatiana; Grineva, Elena; Belyaeva, Olga; Bystrova, Anna; Jude, Edward B.; Andreeva, Alena; Kostareva, Anna; Pludowski, Pawel (Frontiers in Endocrinology, 2018)
Introduction: Recent studies have demonstrated that vitamin D deficiency contributes to the development of metabolic disorders, including obesity and type 2 diabetes mellitus (T2DM). Several vitamin D receptor (VDR) gene polymorphisms had been described to play a role in these conditions since vitamin D receptors were found in many tissues. The aim of this study was to assess the relationship between vitamin D status and VDR gene polymorphisms with metabolic syndrome (MS) parameters in Russian middle-aged women. Materials and Methods: A total of 697 women aged between 30 to 55 years were included in this cross-sectional study. Serum 25-hydroxyvitamin D (25(OH)D) level and four VDR gene polymorphisms rs1544410 (BsmI), rs7975232 (ApaI), rs731236 (TaqI), and rs2228570 (FokI) were measured. We applied the International Diabetes Federation (IDF) criteria to identify subjects with MS. Results: 9.3% of subjects had normal vitamin D level, while 90.7% were insufficient or deficient. Abdominal obesity (AO) was seen in 75.5%, impaired glucose tolerance (IGT) or T2DM was observed in 33.3%, reduced high-density lipoprotein cholesterol (HDL-C) level in 32.2% and hypertriglyceridemia in 23.4%. Serum 25(OH)D level in women with or without MS did not differ (48.6 ± 1.8 and 51.1 ± 1.5 nmol/l, p > 0.05). Subjects with vitamin D deficiency showed an increased risk of AO [CI 95% 2.23; 1.15–4.30] and low HDL-C [CI95% 2.60; 1.04–6.49] compared to subjects with normal 25(OH)D level. IGT and T2DM risk was increased only when 25(OH)D concentration was less than 39.0 nmol/l [CI 95% 7.17; 2.99–17.7], but risk of MS did not differ in normal vitamin D status subjects and insufficient/deficient ones (p > 0.05). T allele carriers (A) of rs7975232 had higher total cholesterol and low-density lipoprotein cholesterol levels compared with the GG (aa) genotypes. Similarly, GG (BB) genotype carriers of rs1544410 had higher triglyceride levels than subjects with A (b) allele carriers. However VDR gene polymorphisms did not seem to be associated with an increased risk of MS. Conclusions: Vitamin D deficiency, rs7975232, and rs1544410 VDR gene variants are associated with MS parameters in Russian middle-aged women.